2020
DOI: 10.1126/scitranslmed.aay7205
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibition improves cardiopulmonary function in a feline model of diastolic dysfunction

Abstract: Heart failure with preserved ejection fraction (HFpEF) is a major health problem without effective therapies. This study assessed the effects of histone deacetylase (HDAC) inhibition on cardiopulmonary structure, function, and metabolism in a large mammalian model of pressure overload recapitulating features of diastolic dysfunction common to human HFpEF. Male domestic short-hair felines (n = 31, aged 2 months) underwent a sham procedure (n = 10) or loose aortic banding (n = 21), resulting in slow-progressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 87 publications
(75 reference statements)
11
84
1
2
Order By: Relevance
“…Moreover, the alteration of microRNAs, such as down-regulation of miRNA-1 and up-regulation of miRNA-195, controls cardiac hypertrophy, oxidative stress, ischemic susceptibility, and fibrosis in HFpEF through histone modification ( 3 , 6 ). Recently, Wallner et al ( 7 ) reported that inhibition of histone deacetylases (HDAC) activity with suberoylanilide hydroxamic acid improves cardiopulmonary function, i.e., preserved lung structure, compliance, blood oxygenation, and reduced perivascular fluid cuffs around extra-alveolar vessels in HFpEF. Furthermore, Jeong et al ( 8 ) found that HDAC inhibition with ITF2357 (givinostat) ameliorates the impairment of cardiac myofibril relaxation, cardiac fibrosis, and cardiac hypertrophy and changes in cardiac titin and myosin isoform expression in Dahl salt-sensitive rats with HFpEF, indicating that epigenetic regulation also significantly contributes to HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the alteration of microRNAs, such as down-regulation of miRNA-1 and up-regulation of miRNA-195, controls cardiac hypertrophy, oxidative stress, ischemic susceptibility, and fibrosis in HFpEF through histone modification ( 3 , 6 ). Recently, Wallner et al ( 7 ) reported that inhibition of histone deacetylases (HDAC) activity with suberoylanilide hydroxamic acid improves cardiopulmonary function, i.e., preserved lung structure, compliance, blood oxygenation, and reduced perivascular fluid cuffs around extra-alveolar vessels in HFpEF. Furthermore, Jeong et al ( 8 ) found that HDAC inhibition with ITF2357 (givinostat) ameliorates the impairment of cardiac myofibril relaxation, cardiac fibrosis, and cardiac hypertrophy and changes in cardiac titin and myosin isoform expression in Dahl salt-sensitive rats with HFpEF, indicating that epigenetic regulation also significantly contributes to HFpEF.…”
Section: Introductionmentioning
confidence: 99%
“…ª 2021 The Authors EMBO Molecular Medicine 13: e11900 | 2021 note that HDAC inhibitors have been suggested as drugs to treat cardiac diseases (McKinsey, 2012), and Vorinostat was found to improve cardiac function, for example, in models for HF with preserved ejection fraction (Wallner et al, 2018) or MI (Nagata et al, 2019). However, either higher concentrations or longer treatment durations were applied in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Third, functional blockage of NHE1 also prevents activation of the NFAT1/NFAT2/NFAT3 pathway, which would result in the induction of NOS2 expression and nitric oxide production through activation of interleukin-10 (IL-10) 21 , 22 . Finally, NHE1 inhibition also interrupts the activation of HDAC1 (histone deacetylase 1) by NFκB (nuclear factor κ B) downstream of AKT, thus further reducing the oxidative stress produced by HDAC1-mediated acetylation defects 23 , 24 .…”
Section: Discussionmentioning
confidence: 99%